Implementation of Early Syllable Games to Improve Early Childhood Reading Learning - Maria Yudica Dina; Alma Vorfi Lama (Early Childhood Development Gazette, 2025)
This study aims to improve early childhood reading skills through the implementation of an Initial Syllable Game. The importance of this research lies in providing an engaging, play-based strategy that supports early literacy development in a child-centered learning environment. This study employed a descriptive qualitative approach conducted at TK Istana Balita Cheng Hoo involving 26 children in Group A2. Data were collected through observation, interviews, and documentation. The research was implemented using cyclical stages of planning, action, observation, and reflection to systematically evaluate and improve the learning process. Data were analyzed inductively using descriptive qualitative techniques. The findings indicate that the Initial Syllable Game effectively enhanced children’s ability to recognize, identify, and pronounce initial syllables. Improvements were observed in children’s confidence, participation, and reading accuracy, with a gradual increase in performance categories from “needs guidance” to “good” and “very good.” The play-based and interactive nature of the game also fostered motivation and positive classroom engagement. The study implies that structured syllable-based games can serve as an effective instructional strategy for strengthening early literacy skills in kindergarten settings. Furthermore, the cyclical reflective model demonstrated in this research provides a practical framework for teachers to continuously improve classroom instruction through systematic evaluation and adaptation.